Health Education Programme: children’s health and well-being - Olivera, Carolina Maria Xaubet; de Abreu-E-Lima, Fabio Cesar Braga [UNESP]; Galato, Dayani; Frade, Joselia Cintya Quintao Pena; de Queirós, Renata Neres Souza; de Farias, Eliana; Fabrício, Gabriela Santos; dos Santos Melo, Jefferson Rodrigo; de Lima Antunes, Lorrane; de Sousa, Valdir Nunes; dos Santos El Chaer, Gilcilene Maria; Maldonado, Jose Luis Miranda (My University, 2024)
►Background. Health education focuses on the prevention of diseases, and health promotion in different populations, and communities. Main purpose of this feasibility study is to educate school-age children about healthy lifestyles, and the rational, and safe use of medicines. ►Methods. The organizing team developed, in a shared and collaborative way, playful tools that would promote and facilitate the acquisition of information on daily behavior for a healthy life. A questionnaire was developed to evaluate the knowledge acquired during the program. The participants’ opinions on the initiative were collected. ►Results. Thirty-four children participated in the research. On average, participants expressed a 12% improvement in their knowledge after participating in the educational activities. The satisfaction evaluation showed that children became proactive, and influenced their parents regarding the practical application of the health education. The activities were successfully completed according to the research schedule, achievement of the objectives, and target public satisfaction, also with the production of information material for the population. ►Conclusions. Specific objectives have been achieved on paths aimed at educating school-age children on healthy lifestyles and the rational and safe use of medicines, also through the publication of appropriate information material.
Keywords: education for public health; face to face teaching; Health Education; health promotion